INNOVATIVE METHODS IN PEDAGOGY, TRANSLATION, AND FOREIGN LANGUAGE TEACHING IN MODERN EDUCATION (Ustozlar uchun, 2026)
This thesis analyzes innovative methods in pedagogy, translation, and foreign language teaching in modern education. It focuses on active learning, problem-based learning, and technology-assisted instruction. These approaches contribute to the development of students’ communicative competence, critical thinking, and learner autonomy.